2019
DOI: 10.1098/rsbl.2019.0428
|View full text |Cite
|
Sign up to set email alerts
|

A keeper of many crypts: a behaviour-manipulating parasite attacks a taxonomically diverse array of oak gall wasp species

Abstract: Parasites of animals and plants can encounter trade-offs between their specificity to any single host and their fitness on alternative hosts. For parasites that manipulate their host's behaviour, the added complexity of that manipulation may further limit the parasite's host range. However, this is rarely tested. The recently described crypt-keeper wasp, Euderus set , changes the behaviour of the gall wasp Bassettia pallida such that B. pallida … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 20 publications
4
14
0
Order By: Relevance
“…Conservation of host gall morphology suggests that Synergus specialization conforms to the "Enemy Hypothesis" (Bailey et al 2009). That is: galls with similar qualities will exclude certain natural enemies and therefore similar galls will tend to be attacked by the same or similar species (Ward et al 2019). Brookfield (1972) similarly suggested that inquilines and parasitoids of galls depend more on gall morphology than other factors such as gall wasp species or tree host (note, however, that this last is belied by our data).…”
Section: Host Ranges and Axes Of Specializationsupporting
confidence: 50%
“…Conservation of host gall morphology suggests that Synergus specialization conforms to the "Enemy Hypothesis" (Bailey et al 2009). That is: galls with similar qualities will exclude certain natural enemies and therefore similar galls will tend to be attacked by the same or similar species (Ward et al 2019). Brookfield (1972) similarly suggested that inquilines and parasitoids of galls depend more on gall morphology than other factors such as gall wasp species or tree host (note, however, that this last is belied by our data).…”
Section: Host Ranges and Axes Of Specializationsupporting
confidence: 50%
“…This behavior facilitates E. set's escape from the crypt following completion of development (Weinersmith et al 2017). Six other cynipid gall wasp hosts of E. set have recently been identified, all residing on different oak species than B. pallida, and all of which appear to be manipulated to facilitate parasitoid emergence (Ward et al 2019).…”
Section: Hymenopteramentioning
confidence: 99%
“…The parasitoid subsequently emerges from the host's head capsule (Weinersmith et al 2017). E. set infects and manipulates at least six additional cynipid gall wasp hosts infecting other oak species (Ward et al 2019). The finding that E. set manipulates a broad range of cynipid gall wasps (Ward et al 2019), suggests that the mechanism E. set uses to manipulate its host either does not require extreme specialization on host physiology or involves a mechanism common to many gall wasp residents.…”
Section: Putative Natural Enemiesmentioning
confidence: 99%
See 2 more Smart Citations